PROSES PEMBUATAN PERATURAN PEMERINTAH (PP) DAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG (PERPPU) - Aziz, Abdul Malik; Winandi, Woro (JURNAL RECHTENS, 2019)
The emergence of subjective rights by the president must meet the conditions with the presence of danger, compulsive urgency and meaning is not limited by several criteria, but depends on the president's view, because the situation has a different meaning. The process of forming PERPPU began with matters that the president felt required to do so, which the President then assigned to the minister to draft with the Minister of Law and Human Rights, then to convert the PERPPU to president must be approved by the DPR, so it must bediscussed at the DPR plenary meeting. If approved, the PERPPU can become law and if not, the PERPPU must be revoked.Keywords: Coercive Urgency, Perppu, Government regulations